Pre-service teachers’ articulation of their future selves - Blackley, Susan; Bennett, Dawn; Sheffield, Rachel (Australian Institutes for Educational Research, 2018)
Important elements of professional socialisation include a sense of identity or belonging within a professional community and a set of established or expected practices. In the context of pre-service teacher education, opportunities to reflect upon past and current personae and to imagine future possible identities may assist pre-service teachers to maximise their professional socialisation and traverse the threshold from expert student to novice professional. This article reports on findings from the first year of a longitudinal study conducted in a Bachelor of Education Primary degree. Participants were second-year pre-service teachers (N=87). Participant data were collected in Semesters 1 and 2, 2016 using an open-ended survey and interviews conducted prior to and following the first professional experience placement. Participants were invited to draw themselves as a teacher. Following other educational researchers, the study incorporated the drawings as a data source and extended the approach to go beyond inductive coding. This was achieved by incorporating the drawings’ captions and triangulating the data with participants’ responses to the characteristics of effective teachers and their concerns about the forthcoming professional placement. The drawings were not privileged over the text components; rather, they were examined in tandem.